2014
DOI: 10.1158/1078-0432.ccr-13-2659
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Lymph Node Metastases as a Determinant of Colon Cancer Recurrence: Results from a Retrospective Multicenter Study

Abstract: Purpose: Recurrence risk assessment to make treatment decisions for early-stage colon cancer patients is a major unmet medical need. The aim of this retrospective multicenter study was to evaluate the clinical utility of guanylyl cyclase C (GCC) mRNA levels in lymph nodes on colon cancer recurrence.Methods: The proportion of lymph nodes with GCC-positive mRNA (LNR) was evaluated in 463 untreated T3N0 patients, blinded to clinical outcomes. One site's (n ¼ 97) tissue grossing method precluded appropriate lymph … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…More recently, a third study published by the same group (GCC study 3) established that the GCC LNR can predict disease outcome in node-negative colon cancer patients and is a suitable adjunct to traditional histopathology for accurate nodal staging. 36 In this study, high-risk patients (defined as LNR > 0.20) had a 2.5 times higher recurrence risk compared to low-risk (LNR 0.10) patients (HR, 2.53; P ¼ .011) using a 3-level GCC LNR risk group classification. 36 These observations suggest that for patients undergoing postoperative surveillance for colon cancer, GCC RT-qPCR may be useful to detect occult metastases and recurrent disease earlier than other methods.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…More recently, a third study published by the same group (GCC study 3) established that the GCC LNR can predict disease outcome in node-negative colon cancer patients and is a suitable adjunct to traditional histopathology for accurate nodal staging. 36 In this study, high-risk patients (defined as LNR > 0.20) had a 2.5 times higher recurrence risk compared to low-risk (LNR 0.10) patients (HR, 2.53; P ¼ .011) using a 3-level GCC LNR risk group classification. 36 These observations suggest that for patients undergoing postoperative surveillance for colon cancer, GCC RT-qPCR may be useful to detect occult metastases and recurrent disease earlier than other methods.…”
Section: Introductionmentioning
confidence: 66%
“…Reconciliation of this apparent inconsistency relies on the use of a molecular ratio of GCCexpressing LNs divided by the total number of informative LNs to quantify occult metastatic tumor burden across the entire regional LN network to define tumor behavior and disease risk. 35,36 Sargent et al 36 demonstrated that the use of a 3-level GCC LNR risk stratification significantly predicted poorer outcomes in high-risk patients (GCC LNR > 0.2) and provided prognostic information in stage IIA colon cancer beyond current prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tougeron et al [25] retrospectively analyzed 433 patients with stage II or III dMMR colorectal cancer, they found there is no significant difference in DFS. Another research held by Sargent showed that MMR status alone was not significantly associated with the disease recurrence time [26]. Sinicrope et al [27] proved that dMMR showed improved outcome compared with pMMR for time to recurrence, DFS and OS in stage II and stage III disease.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the downregulation of GUCY2C was common to both treatments. This gene is well known for its role in endotoxin-mediated diarrhoea, 24 is a potential colorectal cancer marker, 46 and may be a link between obesity and colorectal cancer. 47 Although GUCY2C expression has been detected in CD34 + progenitor cells in peripheral blood, 48 a possible reflection of immune system status, the presence of GUCY2C transcripts in peripheral blood may also be a consequence of IBD disease processes.…”
Section: Discussionmentioning
confidence: 99%